2017
DOI: 10.1093/inthealth/ihx023
|View full text |Cite
|
Sign up to set email alerts
|

HIV status disclosure, facility-based delivery and postpartum retention of mothers in a prevention clinical trial in rural Nigeria

Abstract: HIV status disclosure at 6 weeks' postpartum was positively associated with facility-based delivery, but not with early postpartum retention. Facilitating HIV status disclosure to partners can increase utilization of facility obstetric services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A pregnant woman with a supportive male partner would be more likely to deliver in a health facility by a skilled health professional. 29 We found out that male partners who had monthly income and saving habit are more likely to be involved in ANC/PMTCT service utilization. Male partners did not have time to attend ANC with their partners since they utilize the time to source money to take care of their families when they have socio-economic difficulties.…”
Section: Discussionmentioning
confidence: 76%
“…A pregnant woman with a supportive male partner would be more likely to deliver in a health facility by a skilled health professional. 29 We found out that male partners who had monthly income and saving habit are more likely to be involved in ANC/PMTCT service utilization. Male partners did not have time to attend ANC with their partners since they utilize the time to source money to take care of their families when they have socio-economic difficulties.…”
Section: Discussionmentioning
confidence: 76%
“…Studies from other parts of sub-Saharan Africa have also reported lower odds of modern contraception uptake among HIV-positive women whose partners were not aware of the women’s HIV status [47–49]. Despite increasing evidence on the association between HIV status disclosure and positive PMTCT outcomes [5052], only two-thirds of HIV-positive African women disclose to their male partners [53]. Reasons for non-disclosure in this population include avoiding blame, divorce, neglect, or domestic violence [54, 55].…”
Section: Discussionmentioning
confidence: 99%
“…Since mother-to-child transmission is still unacceptably high, it is important to identify factors that can improve ART adherence among pregnant women and outcomes of prevention of mother-to-child transmission of HIV (PMTCT) care. One such factor is HIV status disclosure, which has been linked to increased ART adherence [5,6] as well as facility delivery [5,7], early infant HIV testing [8], infant antiretroviral prophylaxis [9,10], and adherence to infant feeding guidelines [11].…”
Section: Introductionmentioning
confidence: 99%